2018
DOI: 10.3897/zookeys.794.29156
|View full text |Cite
|
Sign up to set email alerts
|

A new genus of oonopid spiders from Myanmar (Araneae, Oonopidae)

Abstract: A new genus, Kachinia Tong & Li, gen. n., including two new species, K.putao Tong & Li, sp. n., and K.mahmolae Tong & Li, sp. n., is described from Myanmar. The new genus belonging to the subfamily Oonopinae Simon, 1890, currently is the only member of the Brignolia-Opopaea clade with leg spines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The As for the other Asian oonopid genera, i.e., Kachinia Tong &Li, 2018, andVientianea Tong &Li, 2013, also have heavily sclerotized abdominal scuta and leg spines. Paramolotra gen. nov. are quite different from both genera.…”
Section: Discussionmentioning
confidence: 95%
“…The As for the other Asian oonopid genera, i.e., Kachinia Tong &Li, 2018, andVientianea Tong &Li, 2013, also have heavily sclerotized abdominal scuta and leg spines. Paramolotra gen. nov. are quite different from both genera.…”
Section: Discussionmentioning
confidence: 95%
“…The oonopid fauna of Myanmar has been poorly studied. Up to now, eight species have been reported from Myanmar, i.e., Gamasomorpha inclusa (Thorell, 1887), G. psyllodes Thorell, 1897, G. sculptilis Thorell, 1897, Kachinia mahmolae Tong & Li, 2018, K. putao Tong & Li, 2018, Opopaea kanpetlet Tong & Li, 2020, O. zhigangi Tong & Li, 2020, and Xestaspis parmata Thorell, 1897(Tong et al 2018, 2020WSC 2020). In this paper, a new oonopid genus and two new species collected from Myanmar, are described and illustrated.…”
Section: Introductionmentioning
confidence: 99%
“…Oonopids typically have six large contiguous eyes (Ubick 2005), but some species have only two (Platnick 2000), or lack eyes altogether (Chamberlin and Ivie 1938;Benoit 1964;Baehr and Ubick 2010). Oonopids show other striking morphological features, including some with elongated carapace prongs (Abrahim et al 2012), clypeal prongs (Platnick and Dupérré 2011a) and various cheliceral and endite modifications (e.g., Kranz-Baltensperger 2012;Tong et al 2018). But an even more peculiar morphological feature is the occurrence of male palpal asymmetry, extremely rare in spiders (Huber et al 2007), but found in oonopid genera such as Escaphiella, Paradysderina (Platnick andDupérré 2009, 2011c).…”
Section: Introductionmentioning
confidence: 99%